Nutritional prehabilitation in women with early gynaecological cancer - Ilya Krisnana; Jia-You Ye; Hidayat Arifin (Universitas Airlangga, 2026)
Gynaecological cancers remain a major cause of illness and death among women, and many patients are already malnourished when treatment begins, raising their risk of complications and poorer survival. Nutritional support has traditionally been reactive, delivered after surgery or during therapy. This editorial argues for a shift towards nutritional prehabilitation: the proactive, structured optimisation of a patient's nutritional and metabolic reserve during the interval between diagnosis and the start of treatment. Drawing on evidence from surgical oncology and emerging gynaecological data, it outlines the rationale, core modalities, and supporting trials for embedding nutrition within multimodal prehabilitation, and highlights the limited but growing field-specific evidence and the heterogeneity that constrains it. Nurses are uniquely positioned to lead screening, counselling, and coordinated delivery. Nutritional prehabilitation in early gynaecological cancer is a clinical and research priority that the nursing profession should help to advance.